EVOLUTION OF COMPETITION LAW IN SERBIA - Zdravković, Marija (Law - Theory and Practice, 2010)
Even though Competition law began its outbreak in the Serbian legal arena less than a century ago, it was developing rapidly especially in the last decade maintaining the eu antitrust contours. One would say that it is only now on the right track with enforcement of the new law on Protection of Competition, which makes our legal reality even closer to the eu role model. thus, this law corrected all shortcomings of its predecessor, and only time will tell us more of his future application.